Panel regression with random noise - Gerd Ronning; Hans Schneeweiss (Center for Economic Studies and ifo Institute (CESifo), 2009)
The paper explores the effect of measurement errors on the estimation of a linear panel data model. The conventional fixed effects estimator, which ignores measurement errors, is biased. By correcting for the bias one can construct consistent and asymptotically normal estimators. In addition, we find estimates for the asymptotic variances of these estimators. The paper focuses on multiplicative errors, which are often deliberately added to the data in order to minimize their disclosure risk. They can be analyzed in a similar way as additive errors, but with some important and consequential differences.
Keywords: C13; 330; Panel regression; multiplicative measurement errors; bias correction; asymptotic variance; disclosure control; Panel; Regression; Schätztheorie; Statistischer Fehler; Bias; Theorie